A SYSTEM DYNAMIC APPROACH TO A COMMUNITY-BASED CIRCULAR ECONOMY IN BANYUWANGI DISTRICT - Prastika, Novita Candra (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The circular economy was formed because of a change in concept from a linear economy, this was intended to solve the world crisis related to environmental degradation.. One of the activities that contribute to environmental degradation is economic activity. The purpose of this research is to find out how big the contribution of waste management is to the economy and the environment in Banyuwangi Regency. The method used in this study is the system dynamics qualitative method and uses the causal loop diagram approach. The data analysis technique used is the triangulation method, namely interviews with informants, participant observation and documentation. Based on research, the Banyuwangi government has prepared an Integrated Waste Management Site, Reduce, Reuse, Recycle (WMST3R) for waste management but there needs to be constructive action between the government and stakeholders in implementing a circular economy in the environmental sector, this is to form an attitude of community participation and responsibility against environmental degradation.